Amplification and protein overexpression of cyclin D1: Predictor of occult nodal metastasis in early oral cancer. Issue 2 (21st September 2016) - Noorlag, Rob; Boeve, Koos; Witjes, Max J. H.; Koole, Ronald; Peeters, Ton L. M.; Schuuring, Ed; Willems, Stefan M.; van Es, Robert J. J.
Abstract: Background: Accurate nodal staging is pivotal for treatment planning in early (stage I–II) oral cancer. Unfortunately, current imaging modalities lack sensitivity to detect occult nodal metastases. Chromosomal region 11q13, including genes CCND1, Fas‐associated death domain ( FADD ), and CTTN, is often amplified in oral cancer with nodal metastases. However, evidence in predicting occult nodal metastases is limited. Methods: In 158 patients with early tongue and floor of mouth (FOM) squamous cell carcinomas, both CCND1 amplification and cyclin D1, FADD, and cortactin protein expression were correlated with occult nodal metastases. Results: CCND1 amplification and cyclin D1 expression correlated with occult nodal metastases. Cyclin D1 expression was validated in an independent multicenter cohort, confirming the correlation with occult nodal metastases in early FOM cancers. Conclusion: Cyclin D1 is a predictive biomarker for occult nodal metastases in early FOM cancers. Prospective research on biopsy material should confirm these results before implementing its use in routine clinical practice. © 2016 Wiley Periodicals, Inc. Head Neck 39: 326–333, 2017